Problemas en la determinación de los hechos en sede judicial - Gil, Andrés (2011)
Practical syllogism, which, according to ideological positivism, is the only valid methodology for the application of the law, supports, in the majority of cases, the oversight of extra-legal elements in decisions of law, presenting it as a logical-deductive operation in which the main premise is the current legal norm, the minor premise the relevant facts, and the conclusion the judicial decision. Nevertheless, the proposal of the new hermeneutic philosophy and of some current epistemological theories, allows us to bring to light the difficulties facing the judge when establishing the facts of a case. Thus, in this operation the judge must take recourse in assessments which, in a state of law, imposes on him the obligation to defend his version of the relevant facts.